Lisanne Winslow, A Great and Remarkable Analogy - Cochran, Joseph T. (Jonathan Edwards studies, 2021)
Lisanne Winslow, A Great and Remarkable Analogy: The Onto-Typology of Jonathan Edwards (Gottingen: Vandenhoeck and Ruprecht), 171 pp. Hardcover.